Determinants of Digital Eye Strain Among Office Workers: Individual, Device-Related, and Environmental Factors - Nabilah Nur Hasanah; Iting Shofwati; Yustinus Denny Ardyanto Wahyudiono (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Frequent use of digital devices among office workers contributes to a high risk of Digital Eye Strain (DES), with a reported prevalence of 69.0%, which can adversely affect visual performance, sleep quality, and work productivity. This study aimed to analyze the association between individual, device-related, and environmental factors with DES among office workers using a cross-sectional design involving 66 respondents. Data were analyzed using Chi-square and Mann–Whitney tests. The prevalence of DES was 69.7%, with common symptoms including itchy eyes, eye discomfort, and light sensitivity. Key individual factors significantly associated with DES were unsafe digital device use behavior (OR = 11.25; 95% CI: 1.169–30.280), lack of 20-20-20 rest practice (OR = 10.00; 95% CI: 2.895–30.542), and refractive error (OR = 8.20; 95% CI: 2.287–23.399). Among device-related factors, improper computer screen position (OR = 4.263; 95% CI: 1.323–13.736) was identified as a significant predictor. Environmental factors such as inadequate lighting (OR = 5.455; 95% CI: 1.595–18.657) also showed a strong association with DES. In conclusion, DES among office workers is predominantly influenced by behavioral factors, particularly unsafe digital device use and inadequate eye rest practices, which demonstrated the strongest associations. Preventive strategies should prioritize behavioral interventions, ergonomic improvements, and optimization of workplace environmental conditions.